A (re)positioning of imitation in translation studies: the Murat Davman crime fiction series as an imitative translation - Karabulut, Emine; Karadag, Ayse Banu (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2026)
Scholarly discourse in translation studies continues to engage extensively with the conceptualization, scope, and boundaries of translation. This paper, which we believe contributes to this discourse, seeks to explore & Uuml;mit Deniz's Murat Davman crime fiction series through the lens of 'imitative translation,' as proposed by Leo Tak-hung Chan, and to (re)examine the concept of imitation in translation studies. Initially presented as original within the Turkish literary system, the series faced allegations of being an imitation of Mickey Spillane's Mike Hammer series. This study traces the similarities and differences between the Davman and Hammer series, arguing that the Davman series exemplifies imitative translation. By employing imitative translation as a framework and renewing attention to this age-old concept, the study contributes to Chan's discourse on the inclusion of imitation as a research object and proposes (re)positioning imitation within translation studies. It also highlights how imitative translation enhances our understanding of cross-cultural exchanges.
Keywords: Translation studies; crime fiction; Turkish literary system; imitative translation; imitation; cross-cultural exchanges; Linguistics